Tuberculosis and Sudden Death in Lithuania - Zarembaitė, Gintarė; Žiūkaitė, Gabrielė; Chmieliauskas, Sigitas; Vasiljevaitė, Diana; Laima, Sigitas; Stasiūnienė, Jurgita (Acta medica Lituanica, 2023)
Background: Tuberculosis is one of the most common infectious diseases in the world. 10.6 million people fell ill in 2021 and 1.6 million died from the disease. Lithuania has the third-highest tuberculosis incidence rate per 100,000 and the second-highest mortality rate per 100,000 in EU/EEA countries. During 2015–2021 years, there were 799 deaths of pulmonary tuberculosis in Lithuania. However, the presence of pulmonary tuberculosis is often unknown before death and is only revealed during autopsy. The aim of the study is to review current literature on this topic and present statistical analysis on evaluated socioeconomical, epidemiological indicators, as well as autopsy findings that may suggest pulmonary tuberculosis infection.Materials and methods: This research was designed as a retrospective study focusing on full forensic pathology autopsies between 2015 and 2021. Of these, 100 cases were randomly selected where the cause of death was tuberculosis diagnosed during post-mortem examination and compared to a control group consisting of 415 cases of sudden death.Results: The study revealed that out of 100 pulmonary tuberculosis cases, 90% were male with the mean age of 53.48 ± 11.12 years old. In the case of sudden death where tuberculosis was found, a significant portion of the sample (91%) was not followed up at any medical institution. Regarding socioeconomic factors, a moderate negative correlation between Lithuania’s gross domestic product and tuberculosis distribution was observed, as well as a weak negative correlation between alcohol consumption (l per capita) in the general population and tuberculosis distribution. The lung weight of the pulmonary tuberculosis group was statistically significantly higher than that of the control group.Conclusions: Tuberculosis remains a major problem in Lithuania and the combination of socioeconomic indicators determines the prevalence of tuberculosis in the country. In cases of sudden death, autopsy helps to identify tuberculosis cases that have not been clinically detected and ensures tuberculosis monitoring. Therefore, the person who performs autopsy remains at high risk of contracting tuberculosis. Furthermore, extreme caution is advised if higher lung weight or hardenings are seen during autopsy because of the possibility of tuberculosis.
Keywords: forensic science; pathology; sudden death; tuberculosis; Mycobacterium